A Guide to the Political Economy of Reforming Energy Subsidies - Simon Commander (Institute for the Study of Labor (IZA), 2012)
Energy subsidies are used widely. Although adverse from an efficiency perspective, subsidies confer private benefits on particular groups and, once introduced, tend to be persistent. This paper examines the reasons why and possible ways of overcoming the barriers to reform. The starting point is to look at the motives lying behind the adoption of energy subsidies. Distributional motives were found to figure prominently while the role of interested parties or lobbies is also common. The paper then looks at the characteristics of countries that use energy subsidies. Countries with weak institutions often non-democracies tend to be associated with higher subsidies. The paper then looks at how country level conditions and constraints can be identified. An analytical-cum-policy framework allowing identification of the key constraints is proposed before turning to the types of policies contingent on institutional capacity that can address those constraints, such as compensating transfers. The paper also indicates how a better understanding of citizens policy preferences and the trade-offs that are likely to be accepted is essential for designing reform.
Keywords: H20; H23; J65; J68; 330; political economy; energy; subsidies; transfers; Energiepolitik; Subvention; Neue politische Ökonomie; Welt